2021
DOI: 10.21273/hortsci15492-20
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Semi-dwarf Apple Rootstocks in Two-dimensional Training Systems

Abstract: In 2014, an intensive multileader apple rootstock orchard trial was established in Trento province, Northern Italy, using dwarf (‘M.9-T337’) and semidwarf rootstocks (‘G.935’, ‘G.969’, and ‘M.116’) and ‘Gala’, ‘Golden Delicious’, and ‘Fuji’ as the scion cultivars. Trees were trained to Biaxis (‘M.9-T337’) and Triaxis systems (‘G.935’, ‘G.969’, and ‘M.116’) with a tree density of 3175 trees and 2116 trees per hectare, respectively, and with a uniform axis (leader) density of 6348/ha. Comparisons across all trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 42 publications
4
7
0
Order By: Relevance
“…However, M.9 was significantly smaller than the other rootstocks. These results aligned with other studies that reported similar patterns when grafted with ‘Goldspur Delicious’, ‘Redspur Delicious’ progeny ( Tworkoski and Miller, 2007 ), ‘Golden Delicious’, ‘Honeycrisp’, and ‘Fuji’ cultivars ( Dallabetta et al, 2021 ). Slow growth has been reported for M.9 under greenhouse conditions ( Valverdi et al., 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…However, M.9 was significantly smaller than the other rootstocks. These results aligned with other studies that reported similar patterns when grafted with ‘Goldspur Delicious’, ‘Redspur Delicious’ progeny ( Tworkoski and Miller, 2007 ), ‘Golden Delicious’, ‘Honeycrisp’, and ‘Fuji’ cultivars ( Dallabetta et al, 2021 ). Slow growth has been reported for M.9 under greenhouse conditions ( Valverdi et al., 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, in our study, 'Aztec Fuji' on G.935N and M.9T337 has similar yields. These contradictions could be because of different groups of rootstocks were used in our study and those of Dallabetta et al (2021) and Auvil et al (2011).…”
Section: Resultsmentioning
confidence: 91%
“…However, in our study, trees on only G.41N had higher yield than those on M.9Pajam2 (Table 1). Also, Dallabetta et al (2021) reported that 'Golden Delicious', 'Gala', and 'Fuji' apples on G.969 and G.935N had more yield than M.9T337. Nevertheless, in our study, 'Aztec Fuji' on G.935N and M.9T337 has similar yields.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported that rootstock genotype can influence key aspects of fruit quality such as fruit size/weight, flesh firmness, soluble solids contents (SSC), color, starch contents, as well as fruit maturity by affecting respiration rate and IEC in different apple cultivars [6,15,[25][26][27][28][29][30][31][32]. For example, 'Pacific Gala' fruit on B.9 and G.30 rootstocks had the highest SSC and starch degradation patterns compared to other rootstocks [33], while 'Delicious' apples were reported to develop yellow background color earlier when grown on M.26 than on M.7 [29], and fruit from trees on M9.T337 had the lowest percentage of red color with 'Fuji' and the highest with 'Gala' when compared with other rootstocks [34]. Furthermore, the fruit of 'Starkspur Golden Delicious' was shown to have higher IEC when grafted on M.26 rootstock [26].…”
Section: Introductionmentioning
confidence: 95%
“…Rootstocks also play a crucial role in controlling tree size and yield. The size of the tree, and consequently tree vigor, is generally expressed as trunk cross-sectional area (TCA) [37,38], and there have been several studies reporting how TCA and yield can be influenced by rootstock genotype [4,10,11,[32][33][34]39,40]. The use of dwarfing rootstocks in apple orchards significantly reduces tree size and yield, allowing for an increased planting density, production efficiency, reduction in input costs and improved apple fruit quality [41,42].…”
Section: Introductionmentioning
confidence: 99%